Motivational factors influencing decision to become mumpreneurs at pusat layanan usaha terpadu nusa tenggara barat province (PLUT NTB) - Logi, Mulawarman (2022)
The discussion regarding the motivational factors in the mumpreneurs concept still lacks official attention among researchers. This study aims to explain motivational factors influencing mothers’ decision to become mumpreneurs in Pusat Layanan Usaha Terpadu Nusa Tenggara Barat (PLUT NTB). This qualitative study used motivational factors theory in the form of push and pull to support the research process and understand the motivational factor among mothers in becoming mumpreneurs. In a mother’s personal life, the presence of family and children is also an interesting issue to provide an in-depth explanation of motivational factors. So, the in-depth interview techniques were applied to ten Indonesian mumpreneurs in Nusa Tenggara Barat (NTB) Province. The findings in this study are explained as follows: first, the push factors of inadequate family income caused the mother’s desire to help her family income so that the family was spared from an economic problem and subsequently, lack of job opportunities due to the low educational level and wanting to have a suitable job. Second, in the pull factors, mumpreneur defined independently in various points of view, including wanting to have own income, to manage own business, to manage own finances, and to increase income. Afterward, doing business at home and balancing the two roles of entrepreneur and mother was the cause of flexibility factors. Third, the mother’s decision to become a mumpreneur had a strong relationship with family and children, and this finding provided a new understanding of the family and children effect on mumpreneur motivation. This study found that in becoming a mumpreneur, a mother’s motivation tended to increase in urgent financial conditions while having a toddler at home. This was caused by the existence of daily necessities and this can also be interpreted as an effort to survive. Fourth, in the government initiative, PLUT NTB was considered a place for learning that was not optimal yet in motivating mothers to open new businesses. The theoretical contribution provided by this research is in the form of understanding how motherhood plays a crucial role in influencing mothers to become mumpreneurs. This motherhood role raises the concern of mothers for the condition of their families and children so that they dare to enter the world of entrepreneurship. Theoretical contributions are also obtained from the role of PLUT NTB as one of the state institutions in Indonesia that participates in maximizing the existence of mumpreneurs in NTB province.